Historical Study: The Dialectic Between Islamic Law And Positive Law In The Model Of Formal And Informal Marriage In Indonesia - Nurul Fikri Ilham Pratama (Riwayat: Educational Journal of History and Humanities, 2023)
The history of marriage law in Indonesia has a long-standing legacy, with legal scholars continuously working to amend old laws into modern ones that possess strong legal foundations and clear legal certainty. However, written law often differs from the law observed in society, especially in civil cases, including marriage. The dualism of laws in Indonesia has led to disparities in the practice of marriage. In Islamic law, marriage is generally considered valid when the conditions and requirements of marriage are met without the need for marriage registration. Many people in Indonesia still consider Islamic law as the standard for the validity of marriage, making marriage registration seem unnecessary. Meanwhile, positive law on marriage is often viewed as a secondary option, despite the Marriage Law in Indonesia being in effect since 1974. The prevalence of Islamic law, which has been established earlier, has perpetuated the practice of unofficial marriages (sirri). This qualitative research aims to reconcile the asynchrony between these two legal systems, with the hope of raising collective awareness. This includes a critique of positive law, urging its amendment to make marriage registration mandatory for every couple, with sanctions for violators.